Effects from using Ralgro sequentially on sexual development of bulls and on growth and carcass characteristics of steers and bulls - L. Fink; L. Corah; G. Kiracofe; M. McKee (Kansas Agricultural Experiment Station Research Reports, 1979)
Forty-nine Simmental X Hereford and Hereford calves (24 bulls and 25 steers) were used to study the effect of Ralgro on growth, carcass traits, sex drive, sperm production, and development of sex organs. Approximately half of the bulls and half of the steers received a total of four 36-mg. Ralgro implants, one implant each 100 days (approximately 28, 128, 228 and 328 days of age). Implanted bulls and steers had higher average daily gains; however, the effect was greater in steers than bulls. Ralgro impaired all facets of sexual development measured. None of the implanted bulls could have been used for breeding purposes as yearlings.
Keywords: Cattlemen& #x27; s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Sexual development; Bulls; Growth; Carcass characteristics; Steers